The Influence of the Direct Instruction Method on Learning Outcomes of Grade 4 Students at SD Negeri Kadubeureum 1 in Learning Content Natural and Social Sciences - Lestari, Lestari; Maftuhah, Maftuhah; Nurhaliza, Siti (Jurnal Primagraha, 2023)
Much research has been done on learning methods, but this research emphasizes direct interaction methods aimed at fourth grade elementary school students, especially science learning. The type of research conducted is qualitative research. The research method used is the method of interviewing the homeroom teacher and making observations during class learning activities. This research is research that focuses on teachers and students of the Kadubeureum 1 Public Elementary School in Class 4, Serang District. As material for the study of data, researchers conducted data search activities through interviews. Observations and documentation have been carried out during the research and some data that can be presented as data management. From the implementation of the research that has been described in the previous section, it can be concluded that judging from the learning outcomes it can be said that the use of the Direct instruction learning method is optimal for use in science learning in class, because it can exceed the KKM score or the lowest grade limit.